Frozen Section in the Management of Ovarian and Uterine Tumors: The Past 5 Years in a Tertiary Centre - Joana Aidos; Renata Veríssimo; Joana Almeida; Teresa Carvalho; Nuno Nogueira Martins; Francisco Nogueira Martins (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2018)
Abstract Objective Intraoperative frozen section (IFS) is a valuable resource, and its use in gynecological pathology has not been sufficiently emphasized. The main goal of the present study is to evaluate the reliability and agreement rates between IFS and the final paraffin section (PS) and determine how reliable IFS is. Methods A retrospective study of all IFSs performed on uterine tumors and suspicious adnexal masses between January 2012 and December 2016 (excluding metastases) at the department of obstetrics and gynecology of the Centro Hospitalar Tondela Viseu. Frozen versus permanent section diagnosis were compared regarding the histologic type of the tumor, and the depth of myometrial invasion. Results A total of 286 cases were eligible for the present study, including 102 (35.7%) IFSs of uterine tumors, and 184 (64.3%) IFSs of ovarian tumors. The overall rate of deferred cases was 5.2% (15/286). The accuracy of the diagnosis in cases of endometrial carcinoma was 96.25% (77/80). Among the ovarian tumors, misdiagnoses occurred in 2 cases (1.1%), corresponding to a borderline tumor (serous type) and a clear cell intracystic adenocarcinoma. Conclusion The IFS analysis plays an important role in selected situations and is associated to a high sensitivity and specificity in cases of ovarian and endometrial tumors. Its high accuracy is almost universally associated with the possibility of obtaining an optimal surgical treatment at the time of the first surgical approach.